2021
DOI: 10.3390/en14185716
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollutant Emission Abatement of the Fossil-Fuel Power Plants by Multiple Control Strategies in Taiwan

Abstract: This study is an investigation of air pollutant emission abatement in the electricity generation sector from fossil-fuel power plants in Taiwan in 2014 and 2018. PM concentrations are determined by the results of regular tests, while SOx and NOx are determined by continuous emission monitoring systems (CEMS) of flue gas from power plants. The results indicate that electricity generation from fossil-fuel power plants increased by 13.8% from 2014 to 2018. However, emissions of air pollutants from fossil-fuel pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In this section an environmental analysis is done for 1000MWH generated energy from proposed test system and conventional thermal power plant with the help of graphs and table using emission data from 17 19 . Harmful emissions are calculated using Eqs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section an environmental analysis is done for 1000MWH generated energy from proposed test system and conventional thermal power plant with the help of graphs and table using emission data from 17 19 . Harmful emissions are calculated using Eqs.…”
Section: Resultsmentioning
confidence: 99%
“…After going through detailed research survey, it is observed that frequency response under sudden loading can be improved further and hence, In this paper, a detailed analysis of frequency response with proposed controller of 4-FOPID-PSO units fitted in test system having nuclear power plant as a source is done and compared with other controllers fitted with test system under different loading conditions. In this paper, an environmental analysis in terms of harmful emission is done using data from 17 19 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the high temperature inlet flue gas is not conducive to the progress of SO 2 absorption reaction in the desulfurization tower [10][11][12][13], and the water in the limestone slurry in the desulfurization tower evaporates a lot [14]. Therefore, reducing the flue gas temperature at the inlet of the desulfurization tower can improve the desulfurization performance of the desulfurization system and achieve energy saving and consumption reduction [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%